The "Anonymous" sayings of the Desert Fathers: a select edition and complete English translation - Wortley, John (Cambridge University Press, 2013)
The Tales and Sayings of the Desert Fathers (Apophthegmata Patrum) are a key source of evidence for the practice and theory respectively of eremitic monasticism, a significant phenomenon within the early history of Christianity. The publication of this book finally ensures the availability of all three major collections which constitute the work, edited and translated into English. Richer in Tales than the 'Alphabetic' collection to which this is an appendix (both to be dated c.AD 500), the 'Anonymous' collection presented in this volume furnishes almost as much material for the study of the late antique world from which the monk sought to escape as it does for the monastic endeavour itself. More material continued to be added well into the seventh century and so the spread and gradual evolution of monasticism are illustrated here over a period of about two and a half centuries.